Normy fizicheskoj podgotovlennosti gandbolistok vysokoj kvalifikatsii razlichnogo igrovogo amplua - Ignateva, V. J.; Petracheva, I. V.; Savinikov, E. O. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Coaches of teams express the dissatisfaction with the specifications established for players of various game roles. Therefore the big interest represents definition of distinctions in the preparedness of the players who are carrying out various functions in a team. It will enable to reveal some factors of success of performance of modern female handball players in competitions and to offer the optimal specifications of preparedness for the control. The research of physical preparedness in the elite female handball players of different game roles has found out the significant distinctions of their level on some parameters that should lie in the basis of definition of norms of physical preparedness for athletes of this category. On the results of it is necessary to reconsider the represented research the specifications for the control of the physical preparedness, offered by the Union of Russia handballers.